Concentration Quantification of TiO2 Nanoparticles Synthesized by Laser Ablation of a Ti Target in Water - Damjan Blažeka (Materials, 2022)
In this work, we present a quantitative method for determining the concentration of metal oxide nanoparticles (NP) synthesized by laser ablation in liquid. The case study was performed with titanium dioxide nanoparticles (TiO2 NP), which were synthesized by laser ablation of a Ti target in water. After synthesis, a colloidal solution was analyzed with UV-Vis spectroscopy. At the same time, the craters that remained on the Ti target after ablation were evaluated with an optical microscope to determine the volume of the ablated material. SEM microscopy was used to determine the TiO2 NP size distribution. It was found that synthesized TiO2 NP followed a Log-Normal diameter distribution with a maximum at about 64 nm. From the volume of ablated material and NP size distribution, under the assumption that most of the ablated material is consumed to form nanoparticles, a concentration of nanoparticles can be determined. The proposed method is verified by comparing the calculated concentrations to the values obtained from the Beer–Lambert law using the Mie scattering theory for the NP cross-section calculation.